Rejuvenation factor PF4: a potential gatekeeper for neurodegenerative diseases - Jia, Fengju; Shen, Xiaoli (Frontiers in Aging Neuroscience, 2024)
Recently, it is discovered PF4 is a cognitive enhancer that improved the cognitive abilities of younger mice and gave older animals their middle-aged acuity back. PF4 works by reducing inflammation during the aging process. As we all known, aging is undoubtedly the main risk factor of neurodegenerative diseases. Furthermore, inflammation has been extensively investigated and attracted even more interest. Therefore, the aim of the proposal is to highlight the worth of PF4 in inflammaging of neurodegenerative diseases, which might provide a potential therapeutic strategy.